CONFERENCE ABSTRACT BOOK - CONFERENCE ABSTRACT BOOK (International Journal of Applied Pharmaceutics, 2025)
Proceedings of MPCST Sponsored International Conference On "The Future of Drug Safety: From Clinical Trials to Real World